Drone‐Assisted Long‐Distance Delivery of Medical Supplies with Recharging Stations in Rural Communities. - Liu, Jiyang; Ding, Yu; Qiu, Rui; Meng, Zhiyi; Sun, Deguo; Peng, Xinying; Aydin, Mucahit (Health & Social Care in the Community, 2024)
In the past few years, drones have been adopted as a novel delivery tool towards medical supplies, improving delivery service efficiency due to fast speed and neglection of geographical limitations. However, the flight endurance of a battery‐operated drone is limited for long‐distance medical supplies delivery operations. Recharging stations, as a kind of drone facility, allow multiple stops for drones to supplement the power to overcome the flight‐range limitations. This paper studies drone‐assisted long‐distance medical supplies delivery with recharging stations in rural communities by a mixed integer linear programming model. To illustrate the applicability of this model and explore the key factors influencing delivery efficiency of medical supplies, a case study from China is conducted. The results indicate that enhancements on the speed of a truck or a drone can yield considerable delivery cost reduction. In addition, drone‐recharging technology advances can improve delivery efficiency of medical supplies in rural communities.